PREFERENSI MEDIA TEKNOLOGI INFORMASI KOMUNIKASI PADA MAHASISWA PROGRAM NON PENDIDIKAN DASAR UPBJJ-UT MATARAM DALAM MENCARI INFORMASI - Windi Baskoro Prihandoyo (Muhammadiyah University of Mataram, 2016)
Abstract: This study aims to analyze the information and communications technology media preferences of Non Basic Education Program Student in UPBJJ-UT Mataram and analyzes the factors that influence the media preference information communication technology of Non Basic Education Program Student in UPBJJ-UT Mataram. The results in this study is 1) generally known that most respondents own dan able to use information technology communication tools to seek administrative and academic information for higher education at the Open University, 2) generally known that the media of information most used by respondents in the search for administrative and academic information for higher education at the Open University is an Internet, phone and catalog UT.